High sodium chloride concentrations inhibit staphylococcal enterotoxin C gene (sec) expression at the level of sec mRNA. - Regassa, L B (1993)
Expression of the staphylococcal enterotoxin type C gene (sec) is regulated in response to both high NaCl concentrations (osmolarity) and the accessory gene regulator (agr). agr is a global regulator that alters the expression of many genes in Staphylococcus aureus. In this report, we have demonstrated that osmoregulation of sec occurs at the level of mRNA independently of an intact agr allele. Northern (RNA) and Western blot (immunoblot) analyses of samples from cultures grown in low- (0 M NaCl) and high-osmotic-strength (1.2 M NaCl) media revealed that the low-osmotic-strength culture contained approximately 16-fold more SEC and sec mRNA than the high-osmotic-strength culture. sec expression in high-osmotic-strength medium was enhanced when osmoprotective compounds were added. Osmoregulation of sec expression in Agr- strains was also examined; SEC and sec mRNA levels decreased in response to high osmolarity in a manner similar to that seen in the Agr+ strains.